Preparation and characterization of monodisperse solvent-free silica nanofluids. Issue 3 (4th March 2017) - Yang, Shiwen; Tan, Yeqiang; Yin, Xianze; Chen, Shaohua; Chen, Dongzhi; Wang, Luoxin; Zhou, Yingshan; Xiong, Chuanxi
ABSTRACT: A series of solvent-free ionic silica (SiO2 ) nanofluids of 12.3–17.3 nm in diameter were synthesized by surface functionalizing nanoscale SiO2 with a charged corona and ionically tethering with oligomeric chains as canopy. The structure and properties of the nanofluids were systematically characterized by Fourier transform infrared (FTIR), differential scanning calorimeter (DSC), transmission electron microscopy (TEM), thermogravimetric analysis (TGA), and rheology tests. The resultant nanofluids with low-molecular-weight oligomeric as canopy are homogeneous, stable yellow-like fluids with no evidence of phase separation at room temperature, while other nanofluids containing high-molecular-weight as canopy behave like a soft glassy, and they exhibit fluidity with still high modulus and viscosity above 60°C. For deeper understanding of the nature of SiO2 nanofluids, the rheological behavior, thermal stability, as well as morphology of SiO2 nanofluids were investigated in details. The flow properties of nanofluids could be easily regulated from soft glassy to free flowing liquids by varying the molecule weight of canopy. Most importantly, the thermal stability, rheological behavior, as well as morphology can be also regulated through varying molecule weight and thickness of canopy, which will guide our future work on synthesis of nanofluids with controllable physical properties. GRAPHICAL ABSTRACT: